The wings of eagles [videorecording (DVD)] - Ford, John, 1894-1973; Wead, Frank W. (Frank Wilber), 1895-1947; Wayne, John, 1907-1979; Bond, Ward, 1903-1960; Dailey, Dan, 1914-1978; O'Hara, Maureen, 1920-2015 (Turner Entertainment Co. ; Warner Bros. Entertainment : Distributed by Warner Home Video, 2006)
The true story of Naval Commander Frank "Spig" Wead - from his first solo flight that ends in the admiral's swimming pool to his assignment as commander aboard an aircraft carrier in World War II.